CAR-NK for tumor immunotherapy: Clinical transformation and future prospects. (1st March 2020) - Wang, Wenxiu; Jiang, Jingting; Wu, Changping
Abstract: Recently, the use of chimeric antigen receptor-modified T (CAR-T)-cells in the treatment of hematological tumors has been successful and has become a clinical hotspot in tumor immunotherapy. However, their wide application is limited by inherent risks such as graft-versus-host disease (GvHD) and the amount of time it takes to produce CAR-T cells. Natural killer (NK) cells can be xenografted and have the potential to become off-the-shelf products, making CAR-NK cell therapies universal products. These products may be safer than CAR-T cell therapy. Considering that the fundamental researche is still in its infancy, this review focuses on clinical achievements and new strategies for improving the safety and efficacy of CAR-NK cell therapy, as well as the corresponding challenges. Highlights: Targeted lysis of CAR-NK is based on CAR and receptor dependent mechanisms. Achievements of CAR-NK are described in detail in pre-clinical and clinical studies. Introducing IL15, ICR and suicide genes into CAR-NK enhance its safety and efficacy. Advances of CAR-NK will lead tumor immunotherapy into the era of precision medicine.